1 / 12

120 likes | 436 Vues

Multiplying and Dividing Powers. Section 8.2. Multiplying Powers. When 2 powers have the same bases, the powers can be multiplied. a³•a² To do this, keep the base the same and add the exponent. a²⁺³ or a⁵ 3³•3² 3²⁺³ or 3⁵. Simplify Each Expression. 4³•4⁵ 4³⁺⁵ or 4⁸ x³•x⁴

Télécharger la présentation
## Multiplying and Dividing Powers

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Multiplying and Dividing Powers**Section 8.2**Multiplying Powers**When 2 powers have the same bases, the powers can be multiplied. a³•a² To do this, keep the base the same and add the exponent. a²⁺³ or a⁵ 3³•3² 3²⁺³ or 3⁵**Simplify Each Expression**4³•4⁵ 4³⁺⁵ or 4⁸ x³•x⁴ x³⁺⁴ or x⁷ 4y³•y⁴ 4y³⁺⁴ or 4y⁷ (4y²)(3y) (4•3)(y²⁺¹) 12y³**Your Turn!**10⁴•10² 10⁴⁺² 10⁶ y²•y⁴ y²⁺⁴ y ⁶ (-3x²)(5x) (-3•5)(x ²⁺¹) (-15)(x³ ) -15x³ (x⁵y²)(x²y⁴) (x⁵⁺²)(y⁴⁺²) x⁷y⁶**Dividing Exponents**• You can divide posers with the same base by subtracting the exponents a⁵ a² = a⁵⁻² =a³ Think about it: a aaaa a a**Dividing Exponents**5⁷ 5⁴ =5⁷⁻⁴ =5³ x⁶y⁴ xy² =x⁶⁻¹y⁴⁻² =x⁵y²**Simplify Each Expression**4x⁷ 4x⁴ (4 4) and (x⁷⁻⁴) =x³ 8m⁴n⁵ 2m³n² (8 2) and (m⁴⁻³) and (n⁵⁻²) = 4m¹n³ Now, SIMPLIFY! 4mn³**Your Turn!**10⁵ 10² = 10⁵⁻² = 10³ y⁵ y⁴ = y⁵⁻⁴ = y ¹ = y a⁴b⁸ ab² = a⁴⁻¹ and b⁸⁻² = ab⁶ -30m⁵n² 10m³n (-30 10) & m⁵⁻³ & n²⁻¹ = -3m²n**Remember…**• Any base with an exponent of zero will always equal 1! a⁰ = 1 100⁰ = 1 (-12ab)⁰ = 1**More Practice**a³b⁴ a³b (a³⁻³ )(b⁴⁻ ¹) a⁰b³ SIMPLIFY = b³ (Remember a⁰ = 1) 10x⁴y³ 5x⁴y² (2)(x⁴⁻⁴)(y³⁻²) 2x⁰y ¹ SIMPLIFY = 2y**Review**• Simplify Each Expression y²•y⁵ =y⁷ (t²)(t²)(t) =t⁵ (3a²)(4a³) =12a⁵ n⁸ n⁵ =n³ ab⁵c ac =b⁵ ¾a(12b²) =9ab²**Homework **Pg. 344 3-14all, 16-44even

More Related